Variation Law of Infrared Radiation Temperature of Unloading Fracture of Composite Coal-Rock. (14th August 2021) - Li, Xin; Wang, Xue; Yang, Zhen; Li, Hao; Li, Yan; Sun, Weiman
Abstract : For composite mining coal-rock dynamic disaster, combining the theory of thermodynamics, damage mechanics, and other disciplines, the thermodynamic coupling mathematical model of composite coal-rock under an unloading condition is deduced, and the simulation model of composite coal-rock is established for numerical simulation. And the variation law of thermal infrared radiation under triaxial loading and unloading of composite coal-rock is analyzed and verified by experiments. The results show the following findings: (1) The distribution of thermal infrared radiation temperature of composite coal-rock is different in different stages of stress. The overall temperature of the temperature field is lower than the initial temperature field in the three-dimensional stress loading stage and the stage of stress-keeping pressure, but the internal temperature of the coal body is the highest. In the first stage of "loading and unloading, " the temperature of a coal seam increases slightly, and the temperature of other parts of the rock layer increases except for the circular low-temperature zone. In the second stage of "loading and unloading, " an alternating zone of high and low temperatures appears in the rock mass, and the temperature field is enhanced, among which the temperature field reaches the strongest after unloading the confining pressure. After jumping over the maximum stress, the temperature field decreases as a whole at the instability and rupture stage. (2) The variation of surface average thermal infrared radiation temperature (T ave ) of composite coal-rock can be divided into the initial fluctuation stage, the linear heating stage, the local decline stage, the temperature sudden increase stage, and the fracture decline stage. At three different unloading rates of 0.003 MPa/s, 0.03 MPa/s, and 0.05 MPa/s, the T ave of coal body, floor rock, and roof rock reach the maximum before composite coal-rock instability and fracture, and the temperature change of the coal body is the most obvious. (3) Under different confining pressure unloading rates, the T ave of roof rock, coal body, and floor rock shows a strong linear relationship with stress after linear fitting. And the correlation between simulation and experimental results after fitting is above 0.89. The larger the confining pressure unloading rate is, the shorter the peak time of T ave arrives, and the larger the peak value. The comparison between the experimental results and the simulation analysis shows that the two results are consistent, and the research results can provide a theoretical basis for the prevention and control of dynamic disasters in coal and rock mining.